Physiological and Psychological Effects on Heat Acclimatization in Extreme Hot Environment - M. S., Norhidayah; A., Norhidayah (2015)
A cross sectional study of physiological and psychological effects on heat acclimatization in hot environment was conducted among construction workers in Pahang, Malaysia. The goals of this study are to assess the physiological (blood pressure, heart rate and oral temperature) and psychological (fatigue feeling) effects of workers in hot environment. A correlation between fatigue feeling and physiological effects is determined. An increment of physiological parameters toward exposure of heat environment proves that the workers are affected by heat acclimatization. The finding of this study reveals that there are significant differences between before and after session of oral temperature (p=0.0001), heart rate (p=0.0001), systolic blood pressure (p=0.0001), diastolic blood pressure (p=0.001) and sweating rate (p=0.004) among the workers who are working in hot environment. The relationship between fatigue and physiological effects reveals with spearman test that the correlation is weak (p < 0.05). The results show that the physiological changes happen during workers conducted their jobs under hot environment. Only physiological of workers were shifted to achieve the heat acclimatization in extreme hot environment.